Vespa as a Reflection of the Self: Exploring Employee Identity in the Workplace - Saputra, Pramana (Universitas Tanjungpura, 2026)
This study examines how Vespa ownership functions as a form of identity work within the workplace. Moving beyond utilitarian perspectives, the research conceptualizes Vespa as a symbolic artifact through which employees construct, negotiate, and perform professional identity. Using a qualitative design and Interpretative Phenomenological Analysis (IPA), in-depth interviews were conducted with eight Vespa-owning professionals in Pontianak, Indonesia. The findings reveal that Vespa ownership operates across four interrelated dimensions: as a symbol of achievement and aesthetic distinction; as a medium of professional self-presentation; as a catalyst for social connectedness within organizational settings; and as an extension of professional identity. The study demonstrates that material possessions can mediate the relationship between personal authenticity and organizational culture, contributing to both individual meaning making and workplace cohesion. By situating symbolic consumption within organizational life, this research extends theories of the extended self and identity work, offering new insights into how lifestyle symbols shape professional self-construction in contemporary workplaces.